Recruiting and Educating Participants for Enrollment in HIV-Vaccine Research: Ethical Implications of the Results of an Empirical Investigation. (29th July 2013) - Sifunda, Sibusiso; Reddy, Priscilla; Naidoo, Nasheen; James, Shamagonam; Buchanan, David
Abstract: The study reports on the results of an empirical investigation of the education and recruitment processes used in HIV vaccine trials conducted in South Africa. Interviews were conducted with 21 key informants involved in HIV vaccine research in South Africa and three focus groups of community advisory board members. Data analysis identified seven major themes on the relationship between education and recruitment: the process of recruitment, the combined dual role of educators and recruiters, conflicts perceived by field staff, pressure to achieve recruitment targets, problems in achieving comprehension, accountability and education as capacity building. The results raise ethical concerns about the adequacy of current informed consent processes in these settings. The study findings bear directly on current debates about issues of exploitation and the scope of moral responsibilities of researchers and funding agencies to assure that HIV clinical prevention research is conducted ethically.